The impact of biochars on sorption and biodegradation of polycyclic aromatic hydrocarbons in soils-a review - Anyika, Chinedum (Springer Verlag, 2015)
Amending polycyclic aromatic hydrocarbon (PAH)-contaminated soils with biochar may be cheaper and environmentally friendly than other forms of organic materials. This has led to numerous studies on the use of biochar to either bind or stimulate the microbial degradation of organic compounds in soils. However, very little or no attention have been paid to the fact that biochars can give simultaneous impact on PAH fate processes, such as volatilization, sorption and biodegradation. In this review, we raised and considered the following questions: How does biochar affect microbes and microbial activities in the soil? What are the effects of adding biochar on sorption of PAHs? What are the effects of adding biochar on degradation of PAHs? What are the factors that we can manipulate in the laboratory to enhance the capability of biochars to degrade PAHs? A triphasic concept of how biochar can give simultaneous impact on PAH fate processes in soils was proposed, which involves rapid PAH sorption into biochar, subsequent desorption and modification of soil physicochemical properties by biochar, which in turn stimulates microbial degradation of the desorbed PAHs. It is anticipated that biochar can give simultaneous impact on PAH fate processes in soils.